Pengaruh Tingkat Adopsi Budidaya Padi Organik terhadap Keberlanjutan Budidaya Padi Organik di Kabupaten Boyolali - Putri Permatasari; Sapja Anantanyu; Widyatmani Sih Dewi (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Boyolali Regency of Central Java, Indonesia is an area that has developed organic rice cultivation. The development of the adoption rate organic rice cultivation has been conducted since 2009 and still sustainability until today. In fact, not all regions can accept and apply organic rice cultivation. This research was conducted from December 2016 to February 2017 in Boyolali Regency. This research aimed to analyze : (1) the adoption of organic rice cultivation in Boyolali Regency (2) the sustainability of organic rice cultivation in Boyolali Regency (3) the factors affecting the sustainability of organic rice cultivation in Boyolali Regency. This study was quantitative research with explanatory type. The analysis technique employed in this study was a Linear Regression; the sample consisted of 86 farmers living in the Sub Districts having widest organic rice farmland: Sambi, Mojosongo, and Andong. The result of research done by linear regression analysis using SPSS 23,0 program showed that the adoption rate of organic rice cultivation affected directly the sustainability of organic rice significantly with t-test probability (Sign) value of 0,017 less than specified α of 0,05. It indicated that seed preparation, land preparation, seeding, planting, fertilizing and maintenance affected the sustainability of organic rice cultivation in terms of economic and social.